2016
DOI: 10.1371/journal.ppat.1005419
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Modifiers of Natural Killer Cells, Immune Responsiveness and Lymphoid Tissue Remodeling Together Increase Host Resistance to Viral Infection

Abstract: The MHC class I Dk molecule supplies vital host resistance during murine cytomegalovirus (MCMV) infection. Natural killer (NK) cells expressing the Ly49G2 inhibitory receptor, which specifically binds Dk, are required to control viral spread. The extent of Dk-dependent host resistance, however, differs significantly amongst related strains of mice, C57L and MA/My. As a result, we predicted that relatively small-effect modifier genetic loci might together shape immune cell features, NK cell reactivity, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 70 publications
1
14
0
Order By: Relevance
“…In 2016, Gillespie and colleagues analyzed genetic factors that control viral spread during mouse cytomegalovirus (MCMV) infection among different strains of mice, and they showed for mice of an MCMV-resistant strain infected with a high dose of MCMV increased frequencies of NK1.1 + NKp46 + NK cells and corresponding lower viral loads ( 69 ). They concluded that NK cell frequencies and NKp46 + NK cells in MCMV infection depend on distinct loci that regulate NK cells and host resistance ( 69 ). While we also demonstrated highly active NK cells in high-dose infection corresponding with reduced viral loads, the frequency of NK cells in FV-infected mice was not dependent on the infection dose (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Gillespie and colleagues analyzed genetic factors that control viral spread during mouse cytomegalovirus (MCMV) infection among different strains of mice, and they showed for mice of an MCMV-resistant strain infected with a high dose of MCMV increased frequencies of NK1.1 + NKp46 + NK cells and corresponding lower viral loads ( 69 ). They concluded that NK cell frequencies and NKp46 + NK cells in MCMV infection depend on distinct loci that regulate NK cells and host resistance ( 69 ). While we also demonstrated highly active NK cells in high-dose infection corresponding with reduced viral loads, the frequency of NK cells in FV-infected mice was not dependent on the infection dose (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…This shares homology with human CMV and is endemic in wild mice so it is studied in its natural host. Inbred strains of mice that differ in their susceptibility to infection and disease have been used to show how NK and T-cells affect primary infections [4].…”
Section: Introductionmentioning
confidence: 99%
“…In bone marrow chimeric mice expressing MHC I D k solely in hematopoietic or non‐hematopoietic cells, Ly49G2+ NK cells display impaired stimulatory activity, less effective lysis of MHC I‐deficient target cells and diminished MCMV control . Both the frequency and numbers of resting Ly49G2+ NK cells in naïve mice are regulated by MHC I D k , and they additionally undergo specific expansion and accumulation in response to MCMV in MHC I D k mice, but not in mice lacking their cognate self‐MHC I ligand . Moreover, Ly49G2 MA/My or C57L + NK cell responsiveness to MCMV is specifically dependent on the MHC I D k locus .…”
Section: Host Mhc I‐dependent Nk Cell Sensing Of Viral Infectionmentioning
confidence: 99%
“…Both the frequency and numbers of resting Ly49G2+ NK cells in naïve mice are regulated by MHC I D k , and they additionally undergo specific expansion and accumulation in response to MCMV in MHC I D k mice, but not in mice lacking their cognate self‐MHC I ligand . Moreover, Ly49G2 MA/My or C57L + NK cell responsiveness to MCMV is specifically dependent on the MHC I D k locus . NK cells bearing certain Ly49G2 receptor allotypes become licensed when MHC I D k is expressed in both hematopoietic and non‐hematopoietic cells.…”
Section: Host Mhc I‐dependent Nk Cell Sensing Of Viral Infectionmentioning
confidence: 99%